Seasonal distribution of febrile seizure and the relationship with respiratory and enteric viruses in Korean children based on nationwide registry data. (December 2019) - Han, Do Hoon; Kim, Su Yeong; Lee, Na Mi; Yi, Dae Yong; Yun, Sin Weon; Lim, In Seok; Chae, Soo Ahn
Highlights: Febrile seizures were reported to be associated with seasonal viral epidemics. The seasonal distribution of febrile seizures was high from late spring to summer. Influenza virus and enterovirus was most frequently associated with febrile seizure. Abstract: Purpose: The seasonal distribution patterns of febrile seizures and of respiratory and enteric viral pathogens are similar. In this study, we analyzed trends in febrile seizures and viral infection in Korean children, using big data from the Korean Health Insurance Review and Assessment Service (HIRA). Methods: We analyzed children younger than 6 years who visited the hospital and were diagnosed with febrile seizures from 2009 to 2016, using medical records in the HIRA database. A total of 666, 136 medical records of children with a main or subdiagnosis of febrile seizure from 2008 to 2016 were included. Of these records, patients younger than 1 month and records before 2009 were excluded. Finally, 558, 130 records were extracted. Results: The medical records included 315, 774 male children and 242, 356 (43.4%) female children, with a mean age of 2.31 ± 1.31 years. The annual incidence of febrile seizure was 25.4 per 1000 person-years (27.9 for boys and 22.7 for girls). The ratio of male to female children was 1.30: 1, and records of 1-year-old children comprised the highest proportion (n = 210, 400, 33.70%). The total monthly number of patients was highest in May (n = 64, 969, 11.6%), and peaks were formed from April to July. The fewest patients were seen in October (n = 34, 424, 6.17%). The most common viral pathogens were influenza in April and enterovirus during May–July. Conclusion: The seasonal distribution of febrile seizures was high from late spring to summer, and influenza virus and enterovirus were most frequently associated.